Simulation of hydraulic fracture initiation and propagation for glutenite formations based on discrete element method - Tan, Peng; Chen, Gang; Wang, Qian; Zhao, Qing; Chen, Zhaowei; Xiang, Degui; Xu, Chaolan; Feng, Xiao; Zhai, Wenbao; Yang, Zixuan; Shan, Qinglin (Frontiers in Earth Science, 2023)
The existence of gravel in the glutenite formations leads to the complex geometries of hydraulic fracturing propagation and difficult construction in fracturing engineering. To study the hydraulic fracturing propagation law of glutenite formations, this paper establishes a fracture propagation model for the heterogeneous glutenite formations based on discrete element method, and analyzes the effects of gravel content, particle size, distribution, horizontal stress difference, fracturing fluid viscosity and flow rate on hydraulic fracturing propagation. The results show that the complex geometries of hydraulic fractures in glutenite formations can lead to the generation of branched fractures and fracture bifurcation. Small-sized gravels have little effect on the fracture propagation shape which leads to a single main fracture with a flat fracture surface, on the contrary, large-sized gravels may induce hydraulic fractures to deflect along the gravel interface and form branch fractures with distorted fracture surfaces. Hydraulic fractures can propagate around gravel under the condition of high stress difference, high viscosity and medium flow rate. Gravel can prevent the propagation of hydraulic fractures under low stress difference, low viscosity and small flow rate. Hydraulic fracture bifurcation can occur when encountering gravels under high stress difference and large displacement. Properly increasing the high viscosity of fracturing fluids can effectively promote the main hydraulic fracture propagation and reduce the fracture tortuosity, thereby avoiding sand up.